Pertumbuhan Kaempferia rotunda L. dengan Perlakuan Variasi Jumlah Umbi Semu dan Penambahan Pupuk Organik - Ning Wikan Utami (Universitas Atma Jaya Yogyakarta, 2005)
Kaempferia rotunda, usually called as temu putih is belonging into Zingiberaceae family.This plant has been used as traditional medicine for curing diarrhoe and disentry.Objective of the study was to determine the effect of pseudo tubers number and organicfertilizers on the productivity of K. rotunda. Research was conducted in TreubLaboratory, Research Centre for Biology LIPI, Bogor, from July 2002 until April 2003.The experiment was arranged in a factorial Randomized Block Design. The treatmentsconsisted of two factors, i.e the first factor were number of pseudo tubers (0, 2 and 4)and second factor were organic fertilizers (soil, goat manure and compost).The result of the exsperiment showed that both factors, i.e number of pseudo tubers andorganik fertilizers significantly affect productivity of K.rotunda. The effect of goatmanure more dominant than compost. The interaction of those two factors significantlyinfluenced number of leaves and fresh weight of rhizome. The best results was on thecombination treatment of two pseudo tubers and goat manure which had the highestvalue on all peubahs observed which were increased growth and yield of K. rotundasignificantly.